2005
DOI: 10.1128/aem.71.11.7217-7223.2005
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Gene-Based Identification of Midgut Bacteria from Field-Caught Anopheles gambiae Sensu Lato and A. funestus Mosquitoes Reveals New Species Related to Known Insect Symbionts

Abstract: Field-collected mosquitoes of the two main malaria vectors in Africa, Anopheles gambiae sensu lato and Anopheles funestus, were screened for their midgut bacterial contents. The midgut from each blood-fed mosquito was screened with two different detection pathways, one culture independent and one culture dependent. Bacterial species determination was achieved by sequence analysis of 16S rRNA genes. Altogether, 16 species from 14 genera were identified, 8 by each method. Interestingly, several of the bacteria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
172
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(189 citation statements)
references
References 30 publications
13
172
1
3
Order By: Relevance
“…aegypti , Khampang et al 1999, Luxananil et al 2001, Pidiyar et al 2002, Gonzalez-Ceron et al 2003. The microbiota of Anopheles gambiae and Anopheles funestus was also investigated by 16S rDNA sequence by Lindh et al (2005). The objective of this work was to investigate if Ae.…”
Section: We Show For the First Time That The Ventral Diverticulum Of mentioning
confidence: 99%
“…aegypti , Khampang et al 1999, Luxananil et al 2001, Pidiyar et al 2002, Gonzalez-Ceron et al 2003. The microbiota of Anopheles gambiae and Anopheles funestus was also investigated by 16S rDNA sequence by Lindh et al (2005). The objective of this work was to investigate if Ae.…”
Section: We Show For the First Time That The Ventral Diverticulum Of mentioning
confidence: 99%
“…Recent studies showed that one of these factors concerns the primordial role played by the bacteria naturally present in mosquito midgut. Then, there is a growing interest on bacterial biodiversity in Anopheles mosquitoes and particularly those based on the identification of bacteria to be used for malaria transmission blocking based on bacterial genetic changes to deliver antiparasite molecules or paratransgenic approach [5][6][7][8][9][10][11][12][13]. Recent studies reported the presence of symbiotic bacteria, such as Pantoea agglomerans or Asaia in midgut lumen with anti-Plasmodium effector proteins that render host mosquitoes refractory to malaria infection [6,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Entire bacterial communities of insects known to vector bacterial diseases have been described (for example ticks, fleas, and lice), but with very small sample sizes (Reed and Hafner, 2002;Benson et al, 2004;Jones et al, 2008). The bacterial communities of other blood-feeding invertebrates such as mosquitoes and leeches have also been described (Lindh et al, 2005;Worthen et al, 2006); somewhat surprisingly, however, these parasites are not known to vector pathogenic bacterial lineages. An unexplored factor that may affect the ability of pathogenic lineages to colonize and persist within an individual vector is the composition of the vector's bacterial community, whereby certain assemblages of bacteria or non-neutral interactions between specific lineages may alter the ability of specific pathogens to invade the community.…”
Section: Introductionmentioning
confidence: 99%